The Warburg hypothesis and weak ELF biointeractions. (2nd April 2020) - Liboff, Abraham R
ABSTRACT: The Warburg observation concerning ATP generation in cancer cells is analyzed with regard to the likely involvement of H+ resonance effects on the angular velocity of the ATP synthase rotor. It is reasonable to expect that the variety of diseases associated with mitochondrial dysfunction may in part be related to the ATP synthase rate of rotation. Experimental measurements of ATP synthase rotational rates, as found in the literature, are consistent with what might be expected from the ion cyclotron resonance (ICR) frequencies of protons moving under a Lorentz force determined by the approximate surface intensity of the geomagnetic field (~26-65 ?T). One research approach proposes that applying the electronic sum of two critical multiple resonance frequencies simultaneously may serve to more closely resemble real world biochemical changes as compared to applying these frequencies sequentially. Accordingly, it is suggested that applying the sum of the two individual resonance frequencies corresponding to H+ and H3O+ has the capacity to both increase proton density as well as couple to ATP synthase rotation. Not only will this tend to stabilize the F0 rotational rate but also perhaps make it feasible to control this rate, thereby providing a new and potentially efficacious means of treating diseases connected to mitochondrial dysfunction electromagnetically.